(untitled) (Global Journal of Human-Social Science, 2014)
The Niger Delta has for the past two decades been the focus of national and international discuss. The region was virtually ungovernable; enmeshed in panoply of violent conflicts that dove-tailed into near full blown youths driven insurgency. This made the region anarchic and inhospitable for the oil companies. Various studies posit a close link between natural resources and conflict, and oil as being central to conflict. This perspective is underpinned by the greed (economic) model, which posits that conflicts in Africa are greed driven. Militants’ involvement in oil theft has given fillip to the notion that greed underpins insecurity in the Niger Delta. The paper examines the Niger Delta conflicts within the context of the greed model. The paper concludes that insecurity has been goaded by grievance rather than greed as conflicts in the Niger Delta evolved through many stages of oppression, repression and exploitation.